PECULIARITIES OF FORMATION AND DEVELOPMENT OF LOCAL SELFGOVERNMENT AS A SOCIAL INSTITUTION IN KARACHAI-CIRKASSIAN REPUBLIC - Lеilа D. Текееvа (Вестник Северо-Кавказского федерального университета, 2022)
In this article the author considers pre-statist forms of self-organization of the mountainous societies in historical and sociological aspects, including modern stage of institutionalization, peculiarities of formation and functioning of local self-government in the Karachai-Circassian Republic.